An Assessment of the Contributions of 'Ilmiyyah Schools to Arabic and Islamic Learning in the Southern Nigerian Universities - Opeloye, Muhib O. (2014)
This paper attempt to find out how the inclusion of Arabic and Islamic Studies syllabus in the secondary school certificate examination in the early seventies had affected the contributions of the 'ilmiyyah schools to Arabic and Islamic learning in the Southern Nigerian universities.